Correction: Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)

Tree nut alley cropping in Missouri: opportunities across production scales - John Bryan Webber; Nicholas A. Meier; Ronald S. Revord (Agroforestry Systems, 2026)
Missouri has strong potential for expanded tree nut agroforestry, particularly in regions where perennial systems could improve land-use efficiency, reduce erosion risk, and diversify farm income. Alley cropping offers a flexible framework for integrating tree nuts into existing agricultural systems without displacing current enterprises, thereby helping to defray establishment costs and reduce barriers to perennial transition. In Missouri, these opportunities span multiple scales of production, from large-scale row crop systems to small- and medium-scale specialty crop operations. In this perspective, we examine how tree nut alley cropping can be adapted to these different contexts and argue that greater terminological resolution may improve communication, outreach, and research in the United States. Specifically, we propose the terms silvocropping and silvohorticulture to distinguish alley cropping systems that integrate trees with row crops at larger scales from those that integrate trees with intensively managed specialty crops at smaller scales in a temperate growing region. Using Missouri as a representative temperate region for agroforestry adoption, demonstration, and research, we discuss opportunities for hazelnut based systems; conceptual linkages among complementary resource use, land equivalent ratio (LER), and adoption barriers; and the need for research and technical assistance that account for differences in production scale, species composition, and system development over time. Tree nut alley cropping represents an underused opportunity to advance resilient, multifunctional agriculture in temperate regions of the United States.

A Multi-Year Organic Matter Dynamics and Biogeochemical Baseline in the Southeast Clarion-Clipperton Zone - Felipe S. Freitas; Patrick Downes; Alexander P. Webber; Joaquim Bento; Claire Dalgleish; Leigh Marsh; Michael Clarke (Journal of Marine Science and Engineering, 2026)
Organic matter production, recycling, and burial processes temporally fluctuate across the Clarion-Clipperton Zone (CCZ) in the Eastern Tropical Pacific. Between 2019 and 2022, we conducted pelagic and benthic surveys in Nauru Ocean Research Inc. contract area D (NORI-D) in the southeast CCZ to establish environmental baseline conditions. Here, we synthetise the natural ranges of variability in physicochemical and biogeochemical processes in NORI-D across multiple surveys and years. We present interannual water column physicochemical characteristics from five metocean and pelagic campaigns, annual satellite-derived net primary productivity and export production, time-integrated sediment trap annual particulate organic carbon flux, and seafloor biogeochemical and sediment physical characteristics from three benthic campaigns. Temperature and salinity seasonally varied at the sea surface. Strong thermohaline and oxygen stratification developed over 0–100 m. Mean net primary productivity, export production, and seafloor particulate organic carbon flux amounted to 634.1, 15.7, and 2.1 mg C m−2 d−1, respectively. These rates fluctuated nearly four-fold seasonally and interannually. An oxygen minimum zone (100–700 m) dampened organic carbon flux attenuation (b = −0.538) to the abyss. Abyssal seafloor organic matter dynamics showed more homogenous conditions in 2020–2021 (TOC = 0.57 ± 0.05%) than in 2022 (TOC = 0.42 ± 0.19%). Bioturbation rate and mixed-layer depth decreased from 2020 to 2022, while oxygen consumption increased at 0–1 cm bsf. Lipid consumption and compositional alteration in 2022 surpassed 2020–2021. Our findings provide critical baseline data to inform environmental impact assessments and monitoring programmes for deep-sea mining of polymetallic nodules in NORI-D.

Gray whales (Eschrichtius robustus) in San Francisco Bay experience high mortality and have limited affiliation to known foraging groups - Josephine M. Slaathaug; Rebekah S. Lane; William Keener; Alie Pérez; Moe Flannery; Marc A. Webber; Aalea Grimes; Adelle M. Wilkin; Julia E. O’Hern; Pádraig J. Duignan; John Calambokidis; Daniel E. Crocker (Frontiers in Marine Science, 2026)
Terrestrial and marine species are exhibiting distributional shifts due to climate change and resource availability. As food webs are impacted, some species have moved into areas of increased human activity, encountering anthropogenic hazards. A coastal marine species that undertakes a long migration between breeding and foraging ranges, the Eastern North Pacific (ENP) population of gray whales ( Eschrichtius robustus ) is especially vulnerable to changes. Subgroups of ENP gray whales, including the Pacific Coast Feeding Group and the (Puget) Sounders, have adapted to exploit alternative feeding grounds as prey availability declines in the Arctic. Novel to known migration phenology, gray whales have been observed seasonally since 2018 in San Francisco Bay (SF Bay), California. We evaluated subgroup identity and mortality of gray whales in SF Bay from 2018–2025 using photo-identification. Data were collected through vessel-based surveys, opportunistic effort, and community submissions. We identified 114 individual whales of which eight were matched to a subgroup, indicating gray whales utilizing SF Bay are not merely a range extension by foraging subgroups. Only four gray whales were resighted within SF Bay between years. Using photographs, 21 individuals were successfully matched to carcasses and a minimum mortality rate of 18% was determined. Blunt and/or sharp force trauma consistent with vessel strike was determined to be the cause of death for 30 of 70 carcasses, and for nine of 11 matched animals where a cause of death was determined. Sounder and PCFG matched whales were more likely to survive SF Bay than ENP individuals, though minimum length of stay did not influence mortality. This work confirms that gray whales entering SF Bay are highly susceptible to vessel strike mortality and highlights a crucial need to identify and implement adaptive management strategies to mitigate injuries and mortality as whales continue to utilize novel habitat.

Genetic insights into the invasion success of a non-native weed: the case of stinking passionflower (Passiflora foetida sens. lat.) in Australia - Tara Hopley; Bruce L. Webber; S. Raghu; Louise Morin; Margaret Byrne (Biological Invasions, 2026)
The persistence and range expansion of non-native invasive species is in part due to their genetic potential for adaptation in new environments, often associated with reduced competition or predation. The success of a non-native population can be dependent on the initial number of colonising individuals and their genetic diversity, either through the initial introduction or subsequently via multiple introductions across time and space. This study presents research on Passiflora foetida sensu lato, demonstrating the value of analysing the nuclear genome of a non-native invasive weed to complement findings from chloroplast genome analysis. Passiflora foetida is native to the Neotropics, and is a threatening invasive weed targeted for management across northern Australia. Biological control is being explored as a long-term strategy with success more likely when agent selection is informed by introduction history, genetic lineage distribution, and origin of populations of the target weed. This detailed study into the nuclear genomics of P. foetida sensu lato across its non-native range in Australia aimed to determine (1) if the nuclear genome supports earlier genetic insight from chloroplast genome analysis suggesting that there are three genetic entities present in Australia, (2) the distribution of these identified entities, (3) if these entities are segregated or co-located at sites and (4) if there is any evidence of hybridisation. Our nuclear genetic analysis concurred with the chloroplast genome analysis on the presence of three separate genetic entities of P . foetida s. l. in Australia. Several locations were found to have multiple genetic entities present, but limited hybridisation was found between genetic entities. The extensive invasion of P. foetida s.l. in Australia is predominantly being driven by a single entity with very low levels of diversity, as the other two entities had localised distributions in eastern Australia. The low genetic variation present in P. foetida s.l. across the non-native range, and in the regions where the greatest threats from this weed are observed, enables for biological control solutions to be targeted to this entity.

Canapes in the canopy: Canopy macroalgae are dining hotspots for small and juvenile fishes at Orpheus Island, Great Barrier Reef - Kelsey Webber; Katharina Fabricius; Shaun K. Wilson; Dmitry A. Konovalov; Nicoline Winding; Andrew S. Hoey (Marine Environmental Research, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Enabling modeling of waterlogging impact on wheat - Rogério de S. Nóia-Júnior; Valentina Stocca; Pierre Martre; Vakhtang Shelia; Jean-Charles Deswarte; Jean-Pierre Cohan; Benoît Piquemal; Alain Dutertre; Gustavo A. Slafer; Zhentao Zhang; Marijn Van Der Velde; Yean-Uk Kim; et al. (Field Crops Research, 2025)

Wheat crop models underestimate drought stress in semi-arid and Mediterranean environments - H. Webber; D. Cooke; C. Wang; S. Asseng; P. Martre; F. Ewert; B. Kimball; G. Hoogenboom; S. Evett; A. Chanzy; S. Garrigues; A. Olioso; et al. (Field Crops Research, 2025)

Past and future wheat yield losses in France’s breadbasket - Rogério de S. Nóia-Júnior; Pierre Martre; Jean-Charles Deswarte; Jean-Pierre Cohan; Marijn Van der Velde; Heidi Webber; Frank Ewert; Alex C. Ruane; Tamara Ben-Ari; Senthold Asseng (Field Crops Research, 2025)

A techno-economic review of direct air capture of moisture processes: sustainable versus energy-intensive methods - M. Webber; A. Aliyu; S.-H. Jin; M. M. Sadiq; B. Sohani; A. Elseragy (International Journal of Environmental Science and Technology, 2025)
One of the biggest challenges that the world faces today is the availability of fresh and potable water in arid, semi-arid, and deprived regions. This is a challenge that concerns not only economic development but also social development spanning several UN SDGs. This article presents a detailed critical and systematic review of the technologies for producing industrial and potable water. Emphasis is made on direct air capture (DAC) methods as the next frontier in sustainable water production against the backdrop of traditional energy intensive methods such as desalination. Comparisons using a variety of techno-economic, scale, geographic, and environmental metrics are carried out. While market reports suggest that investments and market value of DAC technologies will continuously rise, these data only extend the next 5–10 years. However, using this data, a projection was made by the authors on various scenarios leading to 2050. At 2030, best projections fall short of UN SDG 6 predictions for a four-fold increase (from 2020 levels) required to sustain populations. The review notes that DAC has the potential to be an attractive solution for the current water crisis (in some cases drought) experienced in various regions on earth. The report finds that while several moisture DAC technologies (e.g., fog and dew water harvesting) are currently being developed, they are only being implemented on small scales around the world—with huge implications for arid and deprived regions of the world.

Avocado ( Persea americana Mill) and its phytoconstituents: potential for cancer prevention and intervention - Taylor E. Collignon; Kassidy Webber; Josh Piasecki; Austin S. W. Rahman; Arijit Mondal; Sandra Maria Barbalho; Anupam Bishayee (Critical Reviews in Food Science and Nutrition, 2024)

Utilisation of macroalgal habitats by juvenile rabbitfishes on an inshore reef - Cecilia C. Martin; Eva C. McClure; Kelsey Webber; Martina Burgo; Andrew S. Hoey (Coral Reefs, 2024)
Macroalgal beds are increasingly recognised as nursery habitats for coral reef fish; however, the extent to which they are used as a source of food and/or a refuge from predation remains largely unexplored. Here, we investigate the distribution, feeding behaviour, diet, and predation risk for juvenile rabbitfish in macroalgal habitats on Orpheus Island, Great Barrier Reef. Visual surveys revealed that juvenile and adult Siganus doliatus had different among-habitat distributions with juveniles being largely restricted to the reef flat and positively associated with macroalgal cover, while adults were abundant on the reef crest. Focal feeding observations show that within macroalgal habitats, juvenile S. doliatus targeted epiphytes on Sargassum (80% of bites), with relatively few bites taken on turfs or the Sargassum itself (27% and 8%, respectively). These observations were supported by stomach content analyses with filamentous algae being the dominant item in the stomach content of both small (< 4 cm total length, TL; 58%) and large juvenile S. doliatus (> 4 cm TL; 47%). The stomach content of juvenile S. doliatus, S. canaliculatus, and S. spinus collected from macroalgal habitats was similar, consisting primarily of filamentous algae and detritus. We found no relationship between the abundance of potential predators and juvenile rabbitfishes across the study sites. Collectively, our results suggest that juvenile rabbitfishes are using macroalgal habitats on this, and potentially other, inshore reefs as a food source and add to a growing body of literature highlighting the importance of these habitats for the early life stages of reef fish.

The influence of Sargassum biomass and thallus density on the recruitment of coral reef fishes - Kelsey Webber; Katharina Fabricius; Shaun K. Wilson; Andrew S. Hoey (Coral Reefs, 2024)
A habitat’s structural complexity is a key determinant of the recruitment and composition of associated communities. While the influence of the physical structure of corals on coral reef fish recruitment is well studied, the significance of other benthic components, like macroalgae, remains unclear. We used experimental patches of the canopy-forming macroalga Sargassum to assess the influence of macroalgal complexity, which was manipulated by altering thallus density and biomass, on coral reef fish recruitment. We established twenty-five 75 × 75 cm patches on the reef flat of Orpheus Island, (inshore, central Great Barrier Reef) during austral summer. Patches were randomly divided into five treatments of varying Sargassum thallus density (3–9 thalli) and/or biomass (177–779 g per patch) and surveyed daily for recruiting fishes for 18 d. We recorded 35 fish species recruiting to our patches, with Sargassum biomass having the greatest influence on fish recruits’ abundance and species richness. Comparisons between treatments with equal thallus density but varying biomass revealed a positive association between Sargassum biomass and fish species richness and abundance (up to ~ 2.5-fold differences). Additionally, treatments with similar total Sargassum biomass but different density revealed a negative relationship between density and fish species richness and abundance (20–30% reduction). These positive associations with Sargassum thallus biomass suggest that recruiting fishes favour the fine-scale complexity of intra-thallus spaces, rather than the larger, inter-thallus gaps. This study highlights that fine-scales of complexity within tropical macroalgal beds may influence the reef fish recruitment value of these often-underappreciated areas.

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Mechanisms and modelling approaches for excessive rainfall stress on cereals: Waterlogging, submergence, lodging, pests and diseases - Yean-Uk Kim; Heidi Webber; Samuel G.K. Adiku; Rogério de S. Nóia Júnior; Jean-Charles Deswarte; Senthold Asseng; Frank Ewert (Agricultural and Forest Meteorology, 2024)

Using high-frequency monitoring data to quantify city-wide suspended-sediment load and evaluate TMDL goals - Samuel A. Miller; James S. Webber; John D. Jastram; Marcus F. Aguilar (Environmental Monitoring and Assessment, 2023)
Excess sediment is a common reason water bodies in the USA become listed as impaired resulting in total maximum daily loads (TMDL) that require municipalities to invest millions of dollars annually on management practices aimed at reducing suspended-sediment loads (SSLs), yet monitoring data are rarely used to quantify SSLs and track TMDL progress. A monitoring network was created to quantify the SSL from the City of Roanoke, Virginia, USA (CoR), to the Roanoke River and Tinker Creek and help guide TMDL assessment and implementation. Suspended-sediment concentrations were estimated between 2020 and 2022 from high-frequency turbidity data using surrogate linear-regression models. Sixty-one percent of the total three-year SSL resulted from five large storm events. The average suspended-sediment yield from the CoR (58.1 metric tons/km 2 /year) was similar to other urban watersheds in the Eastern United States; however, the yield was nearly five times larger than the TMDL allocation (12.2 metric tons/km 2 /year). The TMDL allocated load was modeled based on a predominantly forested reference watershed and may not be a practical target for highly impervious watersheds within the CoR. The TMDL model used daily input data which likely does not capture the full range of SSLs during storm events, particularly from flashy urban streams. The average SSL following the five large storm events doubled that of the CoR’s annual allocated load from the TMDL. The results of this study highlight the importance of using high-frequency monitoring data to accurately estimate SSLs and evaluate TMDLs in urban areas.

The extreme 2016 wheat yield failure in France - Rogério de S. Nóia Júnior; Jean‐Charles Deswarte; Jean‐Pierre Cohan; Pierre Martre; Marijn van der Velde; Remi Lecerf; Heidi Webber; Frank Ewert; Alex C. Ruane; Gustavo A. Slafer; Senthold Asseng (Global Change Biology, 2023)
France suffered, in 2016, the most extreme wheat yield decline in recent history, with some districts losing 55% yield. To attribute causes, we combined the largest coherent detailed wheat field experimental dataset with statistical and crop model techniques, climate information, and yield physiology. The 2016 yield was composed of up to 40% fewer grains that were up to 30% lighter than expected across eight research stations in France. The flowering stage was affected by prolonged cloud cover and heavy rainfall when 31% of the loss in grain yield was incurred from reduced solar radiation and 19% from floret damage. Grain filling was also affected as 26% of grain yield loss was caused by soil anoxia, 11% by fungal foliar diseases, and 10% by ear blight. Compounding climate effects caused the extreme yield decline. The likelihood of these compound factors recurring under future climate change is estimated to change with a higher frequency of extremely low wheat yields.

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Contribution of NDM and OXA-type carbapenemases to carbapenem resistance in clinical Acinetobacter baumannii from Nigeria - David O. Ogbolu; Oyebode A. Terry Alli; Adeolu S. Oluremi; Y. Temilola Ogunjimi; D. Iyanu Ojebode; Veronica Dada; Olubunmi O. Alaka; Ebenezer Foster-Nyarko; Mark A. Webber (Infectious Diseases, 2020)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Changes in the population structure and sporulation behaviour of Phytophthora ramorum associated with the epidemic on Larix (larch) in Britain - A. R. Harris; M. S. Mullett; J. F. Webber (Biological Invasions, 2018)

Historical deposits of Alexandrium catenella resting cysts in the sediments of Queen Charlotte Sound, New Zealand - AL MacKenzie; S Webber; AM Watts; A Tonks (New Zealand Journal of Marine and Freshwater Research, 2016)
In 2011, a large repository of resting cysts of the toxic dinoflagellate Alexandrium catenella was discovered in the sediments of the Onapua/Opua inlet located off Tory Channel, Queen Charlotte Sound. The inlet is a potential source of infection for other areas, such as the major mussel‐growing areas of Port Underwood and Pelorus Sound. This study aimed to establish whether the dinoflagellate was a new arrival in the Sounds or had existed unnoticed in this isolated embayment for some time. Alexandrium catenella cysts were identified to a depth of 20–21 cm within the sediment cores, corresponding to a date estimated by radioisotope ( 210 Pb and 137 Cs) and Pinus radiata pollen distribution to at least the mid 1970s. Over this time span, resident populations of A. catenella have not become established beyond the confines of Queen Charlotte Sound, suggesting it does not pose an imminent threat of doing so unless increasingly intense and prolonged blooms result in more widespread cyst dispersal.

Clean energy and water: assessment of Mexico for improved water services and renewable energy - Kelly T. Sanders; Carey W. King; Ashlynn S. Stillwell; Michael E. Webber (Environment, Development and Sustainability, 2013)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

The Energy Return on Investment for Algal Biocrude: Results for a Research Production Facility - Colin M. Beal; Robert E. Hebner; Michael E. Webber; Rodney S. Ruoff; A. Frank Seibert (BioEnergy Research, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

A Framework to Report the Production of Renewable Diesel from Algae - Colin M. Beal; Colin H. Smith; Michael E. Webber; Rodney S. Ruoff; Robert E. Hebner (BioEnergy Research, 2011)

Forecasting emergence and movement of overwintering hazelnut big bud mites from big buds - Janette Webber; R. Bruce Chapman; S. P. Worner (Experimental and Applied Acarology, 2008)

Estimation of walrus populations on sea ice with infrared imagery and aerial photography - Mark S. Udevitz; Douglas M. Burn; Marc A. Webber (Marine Mammal Science, 2008)
Population sizes of ice‐associated pinnipeds have often been estimated with visual or photographic aerial surveys, but these methods require relatively slow speeds and low altitudes, limiting the area they can cover. Recent developments in infrared imagery and its integration with digital photography could allow substantially larger areas to be surveyed and more accurate enumeration of individuals, thereby solving major problems with previous survey methods. We conducted a trial survey in April 2003 to estimate the number of Pacific walruses ( Odobenus rosmarus divergens ) hauled out on sea ice around St. Lawrence Island, Alaska. The survey used high altitude infrared imagery to detect groups of walruses on strip transects. Low altitude digital photography was used to determine the number of walruses in a sample of detected groups and calibrate the infrared imagery for estimating the total number of walruses. We propose a survey design incorporating this approach with satellite radio telemetry to estimate the proportion of the population in the water and additional low‐level flights to estimate the proportion of the hauled‐out population in groups too small to be detected in the infrared imagery. We believe that this approach offers the potential for obtaining reliable population estimates for walruses and other ice‐associated pinnipeds.

Integrated Ecological and Regional Planning in a Rapid-Growth Setting - Kevin S. Hanna; Steven M. Webber; D. Scott Slocombe (Environmental Management, 2007)

A comparative location database (CompLDB): map integration within and between species - Webber Liao; Andrew Collins; Matthew Hobbs; Mehar S. Khatkar; Junhong Luo; Frank W. Nicholas (Mammalian Genome, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

DNA and morphological identification of an invasive swimming crab, Charybdis japonica , in New Zealand waters - P. J. Smith; W. R. Webber; S. M. McVeagh; G. J. Inglis; N. Gust (New Zealand Journal of Marine and Freshwater Research, 2003)
Mitochondrial DNA sequences were used to identify an invasive swimming crab found in Waitemata Harbour, New Zealand. A 457 base sequence of the cytochrome oxidase 1 gene was compared in New Zealand specimens and nine species of Charybdis from Australia and Asia. The New Zealand specimens aligned with C. japonica . The diagnostic morphological characters of C. japonica were also checked in 54 specimens of the species collected in Waitemata Harbour, and concur with the mtDNA result. This is the first record of C. japonica establishing populations outside its native range. C. japonica , along with C. hellerii and the Lessepsian migrant C. longicollis , are the only known invasive species of Charybdis. C. japonica and C. hellerii are two of the few Charybdis species that inhabit the intertidal zone, and it is likely that the intertidal characteristics of these species contribute to their success as invasive species.

Zooplankton growth rates: the influence of size and resources in tropical marine copepodites - R. R. Hopcroft; J. C. Roff; M. K. Webber; J. D. S. Witt (Marine Biology, 1998)

Expression of de novo high-lysine α-helical coiled-coil proteins may significantly increase the accumulated levels of lysine in mature seeds of transgenic tobacco plants - Sharon J. Keeler; Cathy L. Maloney; Patricia Y. Webber; Carole Patterson; Lee T. Hirata; S. Carl Falco; Janet A. Rice (Plant Molecular Biology, 1997)

An improved multi-element measurement of mineral absorption in the piglet utilizing the fecal monitoring technique - Rosalind S. Gibson; Ian L. Gibson; Colin E. Webber; Stephanie A. Atkinson (Biological Trace Element Research, 1988)